Alternative Economic Development Strategies in the Third World: Chile under Salvador Allende Gossens (Journal of Management and Social Sciences, 2019)
The Chilean experiments of formulating and implementing capitalist and socialisteconomic development strategies in the late 50s through early 70s form the core of thisstudy. Because of the commitment of the United States Government to thedevelopment and protection of private property interests and mutatis mutandis, directforeign investments in the Third World, Dr. Salvador Allende's comprehensiveprogramme of socialising the means of production in Chile from 1970â€“1973engendered United States Government's hostile reactions, contributing to Chile'sâ€œinvisible economic blockadeâ€, and eventually, a violent overthrow of the AllendePresidency through a bloody coup de'tat on September 11, 1973. The studyhighlighted the lessons to be learnt from the Allende socialist experiment by any ThirdWorld country.